FITOACUMULATION OF Mn AND Fe ON NYPA FRUTICANS IN TALLO RIVER, MAKASSAR - Zulfikar Zulfikar; Nursiah La Nafie; Syarifuddin Liong (Hasanuddin University, 2018)
The phytoaccumulation of Mn and Fe in nipah palm (Nypa fruticans) has objective to find out the phytoaccumulation potential of Nypa fruticans in Tallo river. Samples were taken in water, sediments, roots, midribs and leaves at five sampling spots representing polluted areas by activities of industrial estates and community settlements. Water was destructed by concentratedHNO3, meanwhile sediments were destructed by dry destruction with aquaregia and plant tissues were destructed by wet destruction with HNO3 6 M and concentrated H2O2, then all the samples were carried on analysis using ICP EOS Shimadzu 9000. The result of analysis has shown that Nypa fruticans was able to accumulate Mn and Fe, moreover the accumulation potential indicated Nypa fruticans able to be natural hyperaccumulator for Fe, otherwise to Mn. According to BCF and TF result were shown the mechanism of phytoaccumulation in Nypa fruticans for Mn and Fe as phytostabilization.